2008
DOI: 10.1038/ng.233
|View full text |Cite
|
Sign up to set email alerts
|

Common variants at CD40 and other loci confer risk of rheumatoid arthritis

Abstract: To identify rheumatoid arthritis risk loci in European populations, we conducted a meta-analysis of two published genome-wide association (GWA) studies totaling 3,393 cases and 12,462 controls1,2. We genotyped 31 top-ranked SNPs not previously associated with rheumatoid arthritis in an independent replication of 3,929 autoantibody-positive rheumatoid arthritis cases and 5,807 matched controls from eight separate collections. We identified a common variant at the CD40 gene locus (rs4810485, P = 0.0032 replicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
424
2
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 475 publications
(471 citation statements)
references
References 30 publications
25
424
2
7
Order By: Relevance
“…7 The association with MMEL1-TNFRSF14 was initially demonstrated in a meta-analysis of three GWAS of approximately 4000 European patients and 12 000 European controls, whereas it had not been detected in any of the smaller individual GWAS. 14 In that study, the minor allele was also shown to have a protective effect on disease development (OR ¼ 0.86), which is similar to what we detect in the current study. The modeling we performed suggested that the homozygous state for the major allele conferred the highest risk, and that the presence of the minor allele was indeed protective in a dominant manner.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…7 The association with MMEL1-TNFRSF14 was initially demonstrated in a meta-analysis of three GWAS of approximately 4000 European patients and 12 000 European controls, whereas it had not been detected in any of the smaller individual GWAS. 14 In that study, the minor allele was also shown to have a protective effect on disease development (OR ¼ 0.86), which is similar to what we detect in the current study. The modeling we performed suggested that the homozygous state for the major allele conferred the highest risk, and that the presence of the minor allele was indeed protective in a dominant manner.…”
Section: Discussionsupporting
confidence: 90%
“…These were selected on the basis of previously published genome wide association data, indicating SNP association with RA. 13,14 Genotyping was undertaken in the laboratory of Dr Katherine Siminovitch at the University of Toronto, and the multiplexed SNP assays were performed on the Sequenom Mass Array iPLEX platform (Sequenom, Inc., San Diego, CA, USA). Allele-specific extension products were plated onto a SpectroCHIP (Sequenom, Inc.) subjected to mass spectrometric analysis, and the genotypes were identified using SpectroCALLER software (Sequenom, Inc.).…”
Section: Snp Testing In Non-hla Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it did not withstand correction for multiple testing, and the risk allele obtained in the present study was contrary to the one reported in the original RA study. 18 We observed a lack of association of IL1A, BANK1, ERAP1 (ARTS1), FAM167A-BLK, CCL21, PTPN2, STEAP1, HERC1 and STAT2 variants with MS. The STEAP and HERC1 variants have been associated with MS in a recent GWAS carried out by the Wellcome Trust Case-Control Consortium based on 12 374 non-synonymous SNPs, 22 but were not validated in our sample set.…”
Section: Kif5a Cd226 and Sh2b3 Variants Associate With Ms A Alcina Ementioning
confidence: 69%
“…29 The association of rs1678542/KIF5A variant with MS, uncovered for the first time in this work, was first associated with RA in European populations. 18,30 The rs1678542/KIF5A is located 194 kb apart from the rs703842/methyltransferase-like protein 1 3 0 UTR with a linkage disequilibrium r 2 of 0.184. The latter polymorphism is the most strongly associated SNP with MS in the locus in the GWAS carried out by the Australia and New Zealand Multiple Sclerosis Genetics Consortium.…”
Section: Kif5a Cd226 and Sh2b3 Variants Associate With Ms A Alcina Ementioning
confidence: 99%